Analisis Tingkat Literasi Digital dan Keterampilan Kolaborasi Siswa dalam Pembelajaran IPA Kelas VII Secara Daring - Qurrota A’yun (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
The purpose of this research was to analyze the profile of digital literacy and student collaboration skills in the online science learning on chapter Interaction of Living Things with the Environment. This research was a descriptive qualitative and conducted from October to November 2019. The instruments were a questionnaire and observation sheet. Both instruments are used to measure the level of digital literacy and collaboration skills. The results obtained were that the students' digital literacy levels were divided into three categories, namely high 69%, medium 18%, and low 13%. Meanwhile, the level of student collaboration skills is also divided into three categories, namely high 72%, medium 23%, and low 7%. The indicators and the item questions from the questionnaires and from the observation sheets can be used as a basis for further research. The conclusion of this research is the digital literacy skill and collaborative skill in the high level with the score of questionnaires and observation sheet.